Research into the Properties of a Composite Material for Microwave Applications Based on PTFE with Different Concentrations and Particle Sizes of Ceramic Filler - A. B. Kozyrev; A. E. Komlev; A. M. Sosunov; A. G. Altynnikov; R. A. Platonov (Известия высших учебных заведений России: Радиоэлектроника, 2023)
Introduction. The technology of printed circuit boards (PCBs) is widely used in modern electronic instrumentation. PCBs for the microwave frequency range are made based on foil composite materials, in particular, polytetrafluoroethylene (PTFE). At the moment, there is no domestic production of such a class of materials. Information concerning foreign manufacturing technologies in this field and the influence of the filler on the characteristics of the composite material remains confidential. Therefore, research into the properties of composite materials for microwave applications with properties similar to foreign analogues seems relevant.Aim. Experimental determination of the dependence of the electrical and mechanical properties of a composite material based on polytetrafluoroethylene depending on the concentration and size of the titanium dioxide fraction.Materials and methods. Experimental determination of the dependence of the electrical and mechanical properties of a composite material based on PTFE depending on the concentration and size of the titanium dioxide fraction.Results. The results of an experimental study of the mechanical properties and microwave parameters of experimental samples of composite material based on PTFE are presented, namely: composite material with 10 % content of ceramic titanium dioxide powders (fraction size 10, 49 and 126 µm); composite material with 5, 10 and 15 % content of ceramic titanium dioxide powder (fraction size 49 µm for polytetrafluoroethylene and 126 µm for titanium dioxide).Conclusion. The results obtained demonstrate prospects for using compositions based on PTFE and titanium dioxide powder as a basis for microwave materials. A correlation was established between the percentage of the introduced ceramic filler and the microwave parameters of the material. The studies demonstrated a slight difference in the microwave properties of the manufactured composite material samples with a different ratio between the particle sizes of titanium dioxide and PTFE. However, a significant decrease in their mechanical properties was observed.